Synthesis, anticancer evaluation and in silico ADMET studies on urea/thiourea derivatives from gabapentin - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH; KARAKUŞ, SEVGİ (TAYLOR & FRANCIS LTD, 2020)
2-(1-((3-Substitutedureido/thioureido)methyl)cyclohexyl)acetic acid derivatives (1-9) were synthesized from gabapentin. All the synthesized compounds were characterized by using IR, H-1-NMR, C-13-NMR spectroscopy, mass spectrometry and elemental analysis. Urea and thiourea derivatives were investigated for their potential in vitro anticancer activities on PC3 and MCF7 cancer cell lines using MTT assay. Cell apoptosis was detected by with Annexin V Assay. Our results showed that compound 8 {2-(1-((3-(2,6-dichlorophenyl)ureido)methyl)cyclohexyl)acetic acid} significantly inhibited the proliferation and growing of PC3 and MCF7 cells. Both cell types showed dysfunction of cellular morphology which induced apoptosis 10 mu M concentration of compound 8 treated cells. Our results indicate that compound 8 might have significance as an anti-tumor agent against human prostate and breast cancer. The theoretical structure and activity estimation via in silico ADMET was also examined.
Keywords: Urea; gabapentin; anticancer; apoptosis; MTT assay